Analisis Intertekstual Timun Mas dan Buto Ijo pada Iklan Marjan dan Cerita Rakyat Indonesia - Devi, Ade Anggraini Kartika; Mawadah, Ade Husnul (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
Abstract This study aims to analyze the intertextuality of Timun Mas and Buto Ijo in the Marjan advertisement with Indonesian folklore. The advertisement is considered as a text derived from the previous text because it uses the characters of Buto Ijo and Timun Mas, namely the legendary figures of folklore entitled Timun Mas and Buto Ijo. The data sources are the Timun Mas and Buto Ijo versions of Marjan advertisements and the Timun Mas and Buto Ijo folk tales. Descriptive analysis was carried out using an intertextuality approach to see the relationship between the two texts. The results showed that the character of Buto Ijo in the Marjan advertisement and Indonesian folklore had some similarities and differences. The similarity is Buto Ijo is tall, big, and green. Buto Ijo, as his name implies, is told as a giant green figure who has great strength. The difference lies at the end of the story. In the advertisement, Buto Ijo has a happy ending by joining the Timun Mas family to celebrate Eid. While in folklore, Buto Ijo has a tragic ending. Buto Ijo died from drowning in a sea of ​​shrimp paste that turned into embers in the ocean.